القوة الناعمة في السياسة الخارجية الليبية تجاه إندونيسيا: جمعية الدعوة الإسلامية العالمية أنموذجا - وحيوني، سري (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
The study focuses on the role of soft power with reference to The World Islamic Call Society in Libyan foreign policy towards Indonesia in pursuit of its interests. This study discusses Libya's diplomatic, cultural and educational relations with Indonesia through the activities The World Islamic Call Society in Indonesia. This study is guided by the conceptual framework composed of national interest, foreign policy analysis and soft power theory. It uses analytical and descriptive methods of data analysis. The data are collected from various sources of news, historical data, interviews and official documents, strategies and activities of The World Islamic Call Society during Colonel Muammar Gaddafi's era. The study discovered that the use of soft power is a successful and effective foreign policy strategy. The Libyan state is competent in using soft power in the application of its foreign policy. The study recommends examining components of soft power in Libyan and Indonesian foreign policy in pursuit of their interests. This study also suggests that the level of soft power in Libya could be improved by focusing on the influence of soft power in regional, global and cultural diplomatic frameworks, as well as utilizing the role of the Islamic Call Society in all its branches.